Tensor network states in time-bin quantum optics - Lubasch, M; Valido, A; Renema, J; Kolthammer, S; Jaksch, D; Kim, M; Walmsley, I; García-Patrón, R (American Physical Society, 2018)
The current shift in the quantum optics community towards experiments with many modes and photons necessitates new classical simulation techniques that efficiently encode many-body quantum correlations and go beyond the usual phase-space formulation. To address this pressing demand we formulate linear quantum optics in the language of tensor network states. We extensively analyze the quantum and classical correlations of time-bin interference in a single fiber loop.We then generalize our results to more complex time-bin quantum setups and identify different classes of architectures for high-complexity and low-overhead boson sampling experiments.